Farm Shop Marketing Strategy Forward Together In Increasing Farmers Purchasing Power - Herlina Herlina (Fakultas Pertanian Universitas Muara Bungo, 2022)
The background of this research is the reduced sales volume at the Advanced Farm Shop because the purchasing power of farmers has decreased. The research objective is to analyze marketing strategies to increase the purchasing power of farmers. Data analysis using SWOT analysis. The results showed that the strategy used was to improve product information services, manage financeswith a mobile application, do internal marketing, have a salesman in every village,and give bonuses forword of mouth activities, making attractive and creative advertisements, lowering market prices and adjusting them to product quality, increasing the benefits of sales channels focusing on product attractiveness, purchasing power, and sales volume, conductingdigital marketing through viral marketing.